Demokrasi Biaya Tinggi: Dimensi Ekonomi dalam Proses Demokrasi Elektoral di Indonesia Pasca Orde Baru - AAGN Ari Dwipayana (Faculty of Social and Political Sciences, Universitas Gadjah Mada, 2009)
Works on contemporary Indonesian democracy are now dominated by a Schumpeterian perspective which emphasizes method and procedure in achieving political decisions. It can be seen from many studies on procedure of participation, political competition, and development of a more plural party system and re-arrangement of representation institutions. Through a more critical point of view on Schumpeterian mainstream, this article explores economic dimension of Post Soeharto Indonesian electoral democracy. This paper discusses why electoral processes are becoming expensive. It also explores how the more expensive electoral processes bring more political corruption in governmental practices.